Automatic Semantic Trend Analysis of the Bled eConference: 2001-2011 - Dreher, Heinz (University of Maribor, 2012)
Semantic analysis algorithms have developed over the last decade to the point where they are almost within reach of everyone, as is Google for text searching. This study reports on an experimental application of automated semantic analysis to the Bled eConference 2001-2011 proceedings full text corpus. Rubrico, the specific tool used in the study is introduced. The methodology used to deploy Rubrico on the Bled corpus for the purpose of revealing the embedded concepts is explained. Interpretation and discussion are offered to indicate the possibilities ensuing from the semantic analysis. Further and future work is indicated to address limitations and further explore the prospects.